Analysis of The Accuracy of Earthquake Parameters In Minahassa Peninsula, Sulawesi, With Seismogram Waveform Data Processing - Triyan, Aldi Muhammad; Suharno, Suharno; Yogi, Ida Bagus Suananda; Wibowo, Rahmat Catur (Journal of Engineering and Scientific Research, 2024)
The Manihassa Peninsula is located in the northern part of Sulawesi, a meeting point for several major tectonic plates, namely the Sunda Plate, the Philippine Plate and the Pacific Plate. The movement and interaction between these plates cause active seismic conditions. Around the Manihassa Peninsula, there are also local faults that can cause earthquakes. This study aims to analyze the accuracy of earthquake parameters published by BMKG by processing waveform data using the author's SeisComP software. This study uses two waveform data of earthquake events in the Minahassa Peninsula of Sulawesi obtained from WebDC3 and processed using SeisComP software with the results of the first earthquake event with an occurrence time of 2024-08-01 00:00:05 UTC, a depth of 146 km, a location point of latitude 0.07 ?S, longitude 123.37 ?E, a magnitude of 5.4 Mw with RMS Res. 1.6 s and Azimuth Gap 144 ? and the second earthquake event with an event time of 2024-08-22 04:43:05 UTC, a depth of 120 km, a location point of latitude 0.09 ?S, longitude 123.50 ?E, a magnitude of 4.7 Mw with RMS Res. 1.0 s and Azimuth Gap 144 ?. From these results, it can be concluded that the search for earthquake parameters that occur using seismogram waveform data on SeisComP software with open-source limitations has quite a good accuracy.